2017
DOI: 10.15294/biosaintifika.v9i2.9285
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Myrmecophytes in Bengkulu Province

Abstract: Myrmecophyte is a common medicinal plant used by local people in Indonesia for treating various diseases especially in Papua. Bengkulu province is one of the Myrmecophyte habitats, but there has no report on its identity and distribution. The objectives of this research were to identify the diversity and analyze the Myrmecophytes distribution as well as factor affecting its presence. This study used purposive sampling method by exploring the area where Myrmecophytes commonly found. The Myrmecophyte distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Myrmecophytes were also found to reside on the main stem of Delonix regia, at the height of 9 to 16 m. Despite growing up on the main stem of Delonix regia, the Myrmecophytes still receive maximum sunlight. This result is consistent with the results of PCA by Safniyeti et al (2017) that shows the intensity of light is the main component of plant II, which affects the existence of Myrmecophytes. In this present study, Myrmecophytes were found in the trees such as Archidendron jiringa, Artocarpus elasticus, Artocarpus integer, Durio sp., Delonix regia, Ficus racemosa, Gmelina arborea, Hevea brasiliensis, and Rhodamnia cinerea.…”
Section: Host Tree Of Myrmecophytessupporting
confidence: 92%
See 2 more Smart Citations
“…Myrmecophytes were also found to reside on the main stem of Delonix regia, at the height of 9 to 16 m. Despite growing up on the main stem of Delonix regia, the Myrmecophytes still receive maximum sunlight. This result is consistent with the results of PCA by Safniyeti et al (2017) that shows the intensity of light is the main component of plant II, which affects the existence of Myrmecophytes. In this present study, Myrmecophytes were found in the trees such as Archidendron jiringa, Artocarpus elasticus, Artocarpus integer, Durio sp., Delonix regia, Ficus racemosa, Gmelina arborea, Hevea brasiliensis, and Rhodamnia cinerea.…”
Section: Host Tree Of Myrmecophytessupporting
confidence: 92%
“…M. tuberosa scattered in clusters in South Bengkulu district and H. formicarum was randomly distributed in four districts in Bengkulu Province (North Bengkulu, Central Bengkulu, Seluma, and Kaur). A previous study of Myrmecophytes occurrence based on their host tree in Bengkulu revealed that 77.8% of the plants spread randomly, and as many as 22.2% spread in groups (Safniyeti et al, 2017). The distribution pattern of Myrmecophytes is influenced by temperature and light intensity in the environment where they grow (Safniyeti et al, 2017).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of observations at the research location show that the distribution pattern is clustered which dominates compared to other distribution patterns. Information the pattern is used to indicate the location of the plant's preferences and is influenced by the variations in soil conditions, resources and competition (Safniyeti et al 2017). The value of the distribution pattern was tried by calculating the Morisita dispersion index (IP) which is presented in Table 2.…”
Section: Distribution Pattern Of Undergrowthmentioning
confidence: 99%